2022
DOI: 10.1021/acs.jmedchem.1c02165
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent, Selective, and In Vivo Efficacious AKT Kinase Protein Degraders via Structure–Activity Relationship Studies

Abstract: We recently reported a potent, selective, and in vivo efficacious AKT degrader, MS21, which is a von Hippel–Lindau (VHL)-recruiting proteolysis targeting chimera (PROTAC) based on the AKT inhibitor AZD5363. However, no structure–activity relationship (SAR) studies that resulted in this discovery have been reported. Herein, we present our SAR studies that led to the discovery of MS21, another VHL-recruiting AKT degrader, MS143 (compound 20) with similar potency as MS21, and a novel cereblon (CRBN)-recruiting PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…Recently, Jin et al reported a potent, selective VHL-recruiting AKT degrader MS143 based on the AKT inhibitor AZD5363. 143 Compared to the inhibitor AZD5363 (AKT1/2/3, IC 50 = 3, 8 and 8 nM, respectively), the most potent degraders MS143 displayed weaker binding affinities to all three AKT isoforms (AKT1/2/3, IC 50 = 26, 400 and 88 nM, respectively). MS143 showed weaker binding affinities but better binding selectivity for AKT1 and 3 over AKT2 (for example, B15-fold and B5-fold binding selectivity with MS143 while B8-fold and B3-fold with derivative (77)) compared to both AZD5363 and its derivative (77), which may be due to the modification of the linker.…”
Section: Design Of Subtype-selective Protacsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, Jin et al reported a potent, selective VHL-recruiting AKT degrader MS143 based on the AKT inhibitor AZD5363. 143 Compared to the inhibitor AZD5363 (AKT1/2/3, IC 50 = 3, 8 and 8 nM, respectively), the most potent degraders MS143 displayed weaker binding affinities to all three AKT isoforms (AKT1/2/3, IC 50 = 26, 400 and 88 nM, respectively). MS143 showed weaker binding affinities but better binding selectivity for AKT1 and 3 over AKT2 (for example, B15-fold and B5-fold binding selectivity with MS143 while B8-fold and B3-fold with derivative (77)) compared to both AZD5363 and its derivative (77), which may be due to the modification of the linker.…”
Section: Design Of Subtype-selective Protacsmentioning
confidence: 97%
“…To selectively block AKT kinase activity, some AKT PROTACs have been reported. [141][142][143] In 2020, Toker et al reported a CRBN-based degrader INY-03-041 (Fig. 11) by conjugating lenalidomide and the most advanced AKT inhibitor (GDC-0068).…”
Section: Design Of Subtype-selective Protacsmentioning
confidence: 99%
“…Of note, INY-03-041 displays more potent effect on suppressing cancer cell proliferation than GDC-0068. Other Akt degraders, MS21 and MS143, which are von Hippel–Lindau (VHL)-recruiting PROTACs based on the Akt inhibitor AZD5363, induce rapid and robust Akt degradation leading to suppressing cancer cell growth and tumor growth in vivo in a xenograft model without causing apparent toxicity [ 152 ]. Further optimization of these degraders will be needed to provide a potential Akt degradation therapy for targeting cancer and various other diseases associate with Akt activation…”
Section: Therapeutic Implications For Cancer Intervention By Targetin...mentioning
confidence: 99%
“…In addition, the novel AKT inhibitor INY-03-041, which is composed of Ipatasertib-NH2, a ten-hydrocarbon linker and a cereblon ligand lenalidomide, can target all three AKT protein for proteasomal degradation [ 143 ]. More and more AKT degraders have been developed [ 144 ]. Preclinical studies demonstrate that these AKT degraders can effectively suppress tumor growth [ 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…More and more AKT degraders have been developed [ 144 ]. Preclinical studies demonstrate that these AKT degraders can effectively suppress tumor growth [ 144 ]. It remains to know whether these compounds are tolerable and have superior efficacy in clinical setting.…”
Section: Discussionmentioning
confidence: 99%